Theoretical growth model space for Cities (Global Journal of Human-Social Science, 2012)
This work raises a theoretical model of spatial growth for the cities in which makes explicit that the growth of population and income growth determined the city s expansion in terms of area built for business and the area destined for housing At the same time shows that local public policy can slow down the growth of the population in the cities by avoiding that generate an unbalanced growth and thus increase the housing deficit
Keywords: City; dynamic urban; growth balanced space; population